Using Digital Learning Platforms to Enhance the Instructional Design Competencies and Learning Engagement of Preservice Teachers - Azza Ali Gameil; Ahlam Mohammed Al-Abdullatif (MDPI AG, 2023)
Given the effects of the COVID-19 pandemic and the associated radical changes to the teaching landscape, employing digital learning platforms in the professional training of teachers has become imperative. The instructional design competencies are among the most important competencies for today's teachers. Therefore, it is necessary to test the effectiveness of digital learning platforms to provide teachers with the required competencies, both cognitive and practical, and to help them improve these competencies. Accordingly, in this study, we aimed to measure the effects of using the Google Classroom platform to develop instructional design competences and learning engagement among preservice teachers in Saudi Arabia. We used a quasi-experimental approach, with a one-group design (pre- and posttest) in this study, which included 61 female student teachers. Three measurement instruments were utilised, namely, the achievement test, the product evaluation card, and the learning engagement scale. The results of our study showed that using Google Classroom as a digital learning platform was effective in helping the preservice teachers acquire and develop their cognitive and practical competencies in instructional design. Our results further revealed high levels of learning engagement at cognitive, behavioural, and social levels among the preservice teachers who participated in learning instructional design through the Google Classroom platform. Our findings emphasise the need for greater investment in digital learning platforms to support preservice teachers' professional training, as these students can benefit from the potential these platforms offer in developing their instructional design competencies.